Status of Science Laboratories in Secondary Basic Education Public Schools in the Division of Davao Del Sur, Philippines (American Journal of Interdisciplinary Research and Innovation, 2024)
The science laboratory became a substantial learning environment for science education, especially in realizing the K–12 science curriculum’s goals, which focus on applying and demonstrating scientific knowledge. Thus, this study aimed to determine the compliance rate of science laboratories in the division of Davao del Sur, Philippines based on DepEd Order No. 48 series of 2006 which entails the prescribed science laboratories in basic education and DepEd Order No. 118 series of 2009 which stipulates the science laboratory equipment and materials. The research examined six schools in three economic categories to assess their science laboratory compliance rate. This study involved creating four matrices containing the prescribed laboratory facilities, equipment, materials, and required quantities for each equipment and material. Results revealed that the compliance rate of the sampled schools in terms of their facilities is 69.04% (good), the equipment is 65.59% (good), the materials are 43.33% (fair), and the compliance with the required quantity is 50.39% (fair). Based on the result of the study, it can be concluded that some schools in the division of Davao del Sur are lacking with the prescribed science laboratory. Thus, it is recommended that the Department of Education, Davao del Sur division to conduct a general assessment of all secondary schools to determine the status of science laboratories’ physical infrastructure, equipment, and materials.